Determination of heavy metals from Aloe vera by- product in golden mullet (Liza aurata); A consumer health risk assessment. (November 2022) - Harb Rabia, Selwan; Luzardo, Octavio P.; Pozo, Raquel; Abbassy, Mostafa; Zumbado, Manuel; Elalfy, Islam; Robaina, Lidia; Ginés, Rafael
Abstract: Heavy metals have become subject of concern in the recent years because of its potency to cause cardiovascular diseases and other toxic health effects. Therefore, this research was assumed to investigate the level of toxicity in terms of heavy metals accumulation in the fish samples and its benefits and risk for human consumers health and also evaluate the partial replacement of plant sources by canarian Aloe vera diets as a pure product or like a by-product on toxicological effects on the golden mullet ( Liza aurata ) fillet and whole body. In this study risks arising from fish metal content has been measured using various parameters as Estimated Daily Intake (EDI), Maximum Safe Consumption (MSCA ), Target Hazard quotient (THQ), Hazard Index (HI) Carcinogenic risk of As (As- CR), the Value Selenium Health Benefit (Se HBV) and also the Nutritional Values has been evaluated. The results showed that all heavy metal levels in the fish tissue and diets were below the confirmed safe limits for consumption. In case of diets, it is obvious that with the exception of As, Hg, and Se, the presence of heavy or essential metals in both whole fish and raw fillet in golden grey mullet given experimental diets revealed that the whole fish had the highest concentration. Thus, it can be concluded that Aloe vera product and byproduct were in safety limits for fish and also for humans through food chain. Various risk and benefit assessment measures established by national and international authorities concluded that Liza aurata use was mostly safe.